Identification of Problems and Needs of Family Members Caring for People with Mental Disorders (ODGJ) - Sandiva Nur Adeni; Mohammad Fatkhul Mubin; Bintang Tatius Nasrullah; Ratih Widayati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Increased awareness of mental health has highlighted the importance of treating mental disorders, including schizophrenia, as a relevant public health problem. The public's view or stigma towards people with mental disorders is that mental disorders still often occur in society. The problems and needs of ODGJ are the cause of family burden. For this reason, this research aims to identify the problems and needs of family members who care for people with mental disorders (ODGJ) in Grobogan Regency. The aim of this research is to identify the problems and needs faced by family members who care for people with mental disorders (ODGJ) in Grobogan Regency. This research is a quantitative descriptive research conducted at Dr. R Soedjati Sumodiharjo Regional Hospital, Grobogan Regency. The sample consisted of 97 respondents who had families with schizophrenia, selected using a sequence sampling technique based on inclusion and exclusion criteria. The instrument used was a standard family burden questionnaire by Wanda K, Mohr, and data analysis was carried out using univariate tests. The results of statistical data analysis show that the majority of respondents experience problems and needs that are in the moderate category. Therefore, treatment and support for families caring for family members with mental disorders needs to pay careful attention to these various factors and adopt a holistic approach to ensure that needs are met. they are well catered for. The conclusion of this study is that families caring for members with mental disorders need better support and interventions, which can be tailored to the context and individual characteristics. A holistic understanding of the characteristics of respondents is key in providing effective support for families who care for family members with ODGJ.